GAME THEORY IN ECONOMICS - Salimov Dilmurat Tajievich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Currently, game theory is used in many sectors of the economy. This article explains how game theory is used in economic systems. This method is based on decision-making under conditions of uncertainty, where one of the players has a certain strategy, and the second one acts randomly. The optimal solution to the problem is determined using several criteria.